Mapping Spatial Distribution of Copper, Dissolved Oxygen and Total Suspended Solids Concentration in Road Stormwater Drainage at Industrial Area - Mohammad, Nur Aina; Khamidun, Mohd Hairul; Abdul Rahman, Mohammad Ashraf; Sanik, Mohd Erwan; Abdullah, Shakila (Journal of Advancement in Environmental Solution and Resource Recovery, 2022)
In present scenario, the urbanization area stormwater quality is decreasing due to human activities such as transportation movement and industrial development. This study was carried out to determine the concentration of water quality parameters such as pH, Dissolved Oxygen (DO), turbidity, Total Suspended Solids (TSS) and copper and to develop the spatial distribution mapping of pH, copper and TSS by using Surfer 8 software. Stormwater samples were collected within 4 weeks from 5 sampling points that had been identified. The experiment tested were conducted according to established technique of the American Public Health Association (APHA, 2012). The results showed that the range reading for pH was 6.48 to 7.60, DO is between 4.45 to 7.49 mg/L, turbidity was ranged 11.94 to 27.16 mg/L, TSS was 11 to 27 mg/L and copper was ranging from 0.19 to 0.27 mg/L. The spatial distribution mapping developed by Surfer 8 software and figure out the trends changing of water quality in the road stormwater drainage. The results showed that the drainage nearest to S3and S5 as most threatened by Cu and lower of DO concentration. The identification of spatial distribution in the study area helps stormwater management to be beneficial in decision-making processes.